Reducing post-harvest losses and enhancing food safety: The role of the midstream traders in the case of mango and vegetable value chains in southern Philippines - Digal, Larry; Carbonell, Alessa Keith; Aguinaldo, Roxanne; Orbeta, Marvin Louie; Shuck, Vlademir; Dijkxhoorn, Youri; Piters, Bart de Steenhuijsen (CGIAR System Organization, 2024)
The agri-food system contributes about a quarter of the country’s gross national product. In Mindanao, its share to the total output is higher being an agri-based economy and when agri-based outputs of the industry and service sectors are accounted for, the share of the agri-food system reaches to more than 60% of its economy (World Bank 2017). An important component of this system is formed by the many informal value chains which include the majority of small-scale farmers and enterprises. Involving actors operating in informal sectors in food system transformation will impact both rural livelihoods and urban food availability. However, these value chains and their principal actors are not well studied in the Philippines particularly their nature, their motivations to remain informal and how to effectively harness their potential particularly in addressing post-harvest waste and losses and food safety.